Strengthening Technology-Based Student Self-Leadership through the Socialization of the Zotero Application in the Islamic Education Management Study Program at IAIN Takengon - Tiarani Mirela; Amiga Putri Minanda; Lailatussaadah Lailatussaadah (al-Afkar, Journal For Islamic Studies, 2026)
The rapid development of technology in the digital era has significantly influenced higher education, including students of the Islamic Education Management (MPI) Study Program at IAIN Takengon. While technology provides broader access to information and learning resources, it also increases the risk of plagiarism due to the ease of obtaining data without proper management. This study aims to describe the strengthening of student self-leadership through the socialization of the Zotero application as a technology-based strategy. Using a qualitative descriptive approach, data were collected through observation, interviews, socialization activities, and documentation. The findings reveal that Zotero socialization positively impacts students’ self-leadership in three aspects: (1) self-awareness, where students recognize the importance of digital reference management as a preventive measure against plagiarism; (2) self-regulation, which enhances their ability to organize learning and writing systematically through library folders and consistent citation practices; and (3) self-motivation, which fosters both internal and external encouragement to produce high-quality academic work. Thus, Zotero functions not only as a reference management tool but also as a medium for cultivating self-leadership relevant to the demands of the digital era. This study concludes that integrating technology into learning supports digital literacy, academic independence, and student productivity, aligning with the vision of the MPI Study Program at IAIN Takengon to produce adaptive and integrity-driven graduates in Islamic education.